2017
DOI: 10.1155/2017/3017608
|View full text |Cite
|
Sign up to set email alerts
|

Improved Backtracking Search Algorithm Based on Population Control Factor and Optimal Learning Strategy

Abstract: Backtracking search algorithm (BSA) is a relatively new evolutionary algorithm, which has a good optimization performance just like other population-based algorithms. However, there is also an insufficiency in BSA regarding its convergence speed and convergence precision. For solving the problem shown in BSA, this article proposes an improved BSA named COBSA. Enlightened by particle swarm optimization (PSO) algorithm, population control factor is added to the variation equation aiming to improve the convergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…COBSA's improvement is achieved through the use of the control factor of the population to the equation of variation. The experiments conducted in [29] indicated that COBSA improved the standard BSA in terms of convergence speed and precision. However, it showed low convergence precision in a few benchmark functions in the experiment compared to other EAs such as ABC and modified ABC (MABC).…”
Section: Performancementioning
confidence: 99%
See 2 more Smart Citations
“…COBSA's improvement is achieved through the use of the control factor of the population to the equation of variation. The experiments conducted in [29] indicated that COBSA improved the standard BSA in terms of convergence speed and precision. However, it showed low convergence precision in a few benchmark functions in the experiment compared to other EAs such as ABC and modified ABC (MABC).…”
Section: Performancementioning
confidence: 99%
“…The proposed technique led to a faster search than the standard BSA. Zhao et al proposed COBSA based on the standard BSA for overcoming the inefficiency of convergence precision and speed in the standard BSA [29]. COBSA's improvement is achieved through the use of the control factor of the population to the equation of variation.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, many improvement research studies have been developed to overcome the drawback. e major modified research studies include the following five categories: (1) modified BSA algorithms by developing hybridization mechanisms [31][32][33][34][35][36][37][38][39], (2) modified BSA algorithms by developing novel initialization mechanisms [40][41][42][43][44][45][46], (3) modified BSA algorithms by developing novel reproduction (mutation or crossover) mechanisms [47][48][49][50][51][52][53][54][55], (4) modified BSA algorithms by developing novel selection mechanisms [56][57][58][59][60], and (5) modified BSA algorithms by developing novel control mechanisms for parameters (including the control factor F which is randomly generated in the original BSA) [61][62][63][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…And two years later, Chen et al [53] proposed a new mutation operator with knowledge learning and adaptive control parameter. Zhao et al [54] introduced population control factor and optimal learning strategy into the mutation process of the BSA to improve the performance of algorithm. Yu et al [55] proposed a multiple learning strategy to replace reproduction mechanism of the original BSA.…”
Section: Introductionmentioning
confidence: 99%